Identification of a new variable number tandem repeat locus in Mycobacterium ulcerans for potential strain discrimination among African isolates - Ablordey, A.; Fonteyne, P.-A.; Stragier, P.; Vandamme, P.; Portaels, F. (Clinical Microbiology and Infection, 2007)
Intra-species discrimination in the highly clonal pathogen Mycobacterium ulcerans was studied in a diverse collection of isolates by PCR amplification of a short sequence repeat locus containing heterogeneous arrays of tri-nucleotide repeats with an ACC consensus pattern. Post-amplification analysis indicated excellent typeability and identified five M. ulcerans alleles, including a unique Angolan type differentiated for the first time among a genetically conserved cluster of African isolates. These results are consistent with previously investigated independent markers, and provide an additional locus for variable number tandem repeat-based typing of M. ulcerans. © 2007 The Authors; Journal compilation © 2007 Blackwell Publishing Ltd.
Keywords: Discrimination; Mycobacterium ulcerans; PCR; Typing; Variable number tandem repeat